From social and natural vulnerability to human-centered climate resilient coastal cities - Niamir, Leila; Pachauri, Shonali (Frontiers in Sustainable Cities, 2023)
Anthropogenic climate change is increasingly affecting every city in the world, including through more intense weather and climate extremes. Climate impacts and risks are magnified in cities, which are home to more than half the world's population. Projections show one billion people will live in areas at risk of coastal hazards by 2050. Sea level rise jeopardizes cities to complicated wind, water, and coastal hazards. Potential impacts on wellbeing include damage to housing, transportation, and energy infrastructure as well as human health. Yet, attention thus far has focused on incremental adaptation responses, with a focus more on infrastructure and technology transitions in coastal cities. Comprehensive transformative actions that specifically incorporate behavioral, cultural and institutional options are largely neglected. In this perspective, we emphasize that immediate and massive effort and involvement from individuals to social entities across sectors, institutions, and systems is required for a transformation toward climate-resilient coastal cities. We conclude by emphasizing that dichotomies between ambitious adaptation and mitigation actions need to be bridged to enhance resilience to warming in coastal cities, and that this requires appropriate multi-level governance mechanisms to coordinate across agents and sectors.